NS1: A Key Protein in the “Game” Between Influenza A Virus and Host in Innate Immunity - Ji, Zhu-xing; Wang, Xiao-quan; Liu, Xiu-fan (Frontiers in Cellular and Infection Microbiology, 2021)
Since the influenza pandemic occurred in 1918, people have recognized the perniciousness of this virus. It can cause mild to severe infections in animals and humans worldwide, with extremely high morbidity and mortality. Since the first day of human discovery of it, the "game" between the influenza virus and the host has never stopped. NS1 protein is the key protein of the influenza virus against host innate immunity. The interaction between viruses and organisms is a complex and dynamic process, in which they restrict each other, but retain their own advantages. In this review, we start by introducing the structure and biological characteristics of NS1, and then investigate the factors that affect pathogenicity of influenza which determined by NS1. In order to uncover the importance of NS1, we analyze the interaction of NS1 protein with interferon system in innate immunity and the molecular mechanism of host antagonism to NS1 protein, highlight the unique biological function of NS1 protein in cell cycle.